Study of influence of regulatory polymorphisms of expression in development of breast cancer - Lopes, Joana Margarida Teixeira (2015)
The human genome has millions of genetics variants that can affect gene expression. These variants are known as cis-regulatory variants and are responsible for intra-species phenotypic differences and individual susceptibility to disease. One of the diseases affected by cis-regulatory variants is breast cancer. Breast cancer is one of the most common cancers, with approximately 4500 new cases each year in Portugal. Breast cancer has many genes mutated and TP53 has been shown to be relevant for this disease. TP53 is one of the most commonly mutated genes in human cancer and it is involved in cell cycle regulation and apoptosis. Previous work by Maia et al has shown that TP53 has differential allelic expression (DAE), which suggests that this gene may be under the influence of cis-regulatory variants. Also, its DAE pattern is totally altered in breast tumours with normal copy number. We hypothesized that cis-regulatory variants affecting TP53 may have a role in breast cancer development and treatment. The present work aims to identify the cis-regulatory variants playing a role in TP53 expression, using in silico, in vitro and in vivo approaches. By bioinformatic tools we have identified candidate cis-regulatory variants and predicted the possible transcription factor binding sites that they affect. By EMSA we studied DNA-protein interactions in this region of TP53. The in silico analysis allowed us to identified three candidate cis-regulatory SNPs which may affect the binding of seven transcription factors. However, the EMSA experiments have not been conclusive and we have not yet confirmed whether any of the identified SNPs are associated with gene expression control of TP53. We will carry out further experiments to validate our findings.